Energy security in the EU beyond - Richard Pomfret (Center for Social and Economic Research (CASE), 2009)
Past episodes of energy insecurity have been fleeting and the fears have been assuaged by market forces or technical change. This paper analyses the nature of the EU's current energy security problems, emphasising the increased importance of natural gas and high level of dependence on Russian supplies through a small number of pipelines. Building alternative pipeline routes is expensive and with finite reserves in any gas field pipelines may be mutually exclusive; especially since China has entered the market for Central Asian gas, new non-Russian pipelines to the EU may not be economically feasible. However, global gas reserves are large, and high energy prices in the 2000s encouraged investment in alternative delivery modes, notable liquefied natural gas (LNG). As a spot market for LNG emerges EU energy-importing countries may face volatile prices, but will not be exposed to insecurity of supply.
Keywords: Q34; L71; N74; 330; natural gas - pipelines - energy security; Energieversorgung; Erdgas; Pipeline; Flüssiggas; EU-Staaten